(untitled) (Eurasian Medical Research Periodical, 2023)
Organization of anti-doping education of students of sports universities assumes the presence of a specialized discipline "Fundamentals anti-doping support". Formation of a number of competencies in students in anti-doping educational areas occurs when mastering both disciplines medical and biological cycle, as well as sports, pedagogical and public disciplines that require or the presence of an erudite teacher with deep and comprehensive knowledge in the field of sports philosophy and psychology, sports law and, simultaneously, in the field of sports biochemistry and sports medicine, or division disciplines on: "Legal basis of anti-doping support" and "Biochemical fundamentals of anti-doping support"